Communication satellite systems for high-speed Internet access. - Evans, J.V.
Communication satellites were originally conceived as a means of providing a voice telephone service over the entire globe, i.e., between countries, which up to that time had no direct links with one another. Subsequently, satellites were launched to provide service to mobile users (the military, ships, aircraft, etc.), and for distributing television programs domestically. In the US, this was initially restricted to feeding cable head-ends, but direct-to-the home TV has become widespread. Satellite service providers now see offering businesses and consumers high-speed access to the Internet and the World Wide Web as the newest opportunity to expand their offerings. This paper reviews efforts now underway by a number of companies to tap this market, some of whom plan to deploy new, special-purpose satellite systems.
Keywords: Satellite communication; Satellite broadcasting; Satellite applications; Satellite mobile communication; Radio spectrum management; Land mobile radio spectrum management; Data communication; Integrated voice-data communication; Land mobile radio data communication